Antihyperlipidaemic effect of triterpenic acid-enriched fraction from Cyclocarya paliurus leaves in hyperlipidaemic rats. (1st January 2017) - Wu, Zhengfeng; Gao, Tianhong; Zhong, Rongling; Lin, Zi; Jiang, Cuihua; Ouyang, Sheng; Zhao, Ming; Che, Chuntao; Zhang, Jian; Yin, Zhiqi
Abstract: Context: Cyclocarya paliurus (Batal) Iljinskaja (Juglandaceae) is an edible and medicinal plant; the leaves are used in Chinese folkloric medicine to treat dyslipidaemia and diabetes. Objective: This study evaluates the antihyperlipidaemic potential of the triterpenic acid-enriched fraction (TAE) from C. paliurus and the underlying mechanism. Materials and methods: The hyperlipidaemic rats were induced by high fat diet for 6 weeks. After oral administration of TAE (200 and 400 mg/kg), the neutral fraction (150 and 300 mg/kg) and statin (4 mg/kg) to the hyperlipidaemic rats for 4 weeks, lipid profile and apolipoprotein (apoB48) level in plasma, and the expression levels of apoB48, microsomal triglyceride transfer protein (MTP), phosphorylation of mitogen-activated protein kinase (MAPK) and tumour necrosis factor α (TNF-α) in intestine were examined. The main constituents in the TAE were identified by HPLC-MS. Results: TAE administration (400 mg/kg) decreased the levels of atherogenic lipids in serum and liver ( p  < 0.05) and increased serum high-density lipoprotein cholesterol by 19.7%. Furthermore, TAE treatment (200 and 400 mg/kg) decreased plasma apoB48 level by 15.3 and 19.5%, downregulated intestinal apoB48 and MTP expression levels ( p  < 0.05), and inhibited TNF-α expression by 36.2 and 56.2% and the phosphorylation level of MAPK by 8.8 and 13.2%, respectively. HPLC analysis revealed the presence of pentacyclic- and tetracyclic-triterpene acids in TAE. Conclusion and discussion: These findings suggested that TAE possessed antihyperlipidaemic activity partially involved in the inhibitory effect on apoB48 overproduction, which may provide evidence about its potential role in ameliorating dyslipidaemia.